2007
DOI: 10.1177/1350506807079012
|View full text |Cite
|
Sign up to set email alerts
|

Les Infirmières Exclusives and Migrant Quasi-Nurses in Greece

Abstract: The article explores the complex experiences and positions of migrant women in the 'nursing profession' in a southern European country, Greece. It looks at ways in which a rudimentary welfare state and a large informal economy have created the demand for les infirmières exclusives and for 'quasi-nurses'. The supply and use of their services, on the one hand, helps perpetuate this informal welfare system and, on the other, has implications for migrant women themselves as, inter alia, it contributes to their des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 14 publications
0
19
0
4
Order By: Relevance
“…Moreover, the PDN system does not support lifelong learning and continuing education. For example, a PDN in the Lazaridis (2007) study reported a single occasion in 3 years where they had been advised how to behave towards a patient. In another instance, a PDN mentioned she had never received any training as a nurse assistant and was never asked if she had any problems or needed any training (Lazaridis 2007).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the PDN system does not support lifelong learning and continuing education. For example, a PDN in the Lazaridis (2007) study reported a single occasion in 3 years where they had been advised how to behave towards a patient. In another instance, a PDN mentioned she had never received any training as a nurse assistant and was never asked if she had any problems or needed any training (Lazaridis 2007).…”
Section: Resultsmentioning
confidence: 99%
“…According to the research findings, PDN responsibilities were to provide hygiene care to the patients, to report emergency needs to staff, to meet the patients' basic needs, such as toileting, assisting patients to eat, administering medicines (mainly orally) and changing dressings (Groutsis 2009; Lazaridis 2007) and to stay awake all night long to take care of them (Lazaridis 2007).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Il est important de garder à l'esprit les interrelations entre les résultats concrets des politiques publiques en matière de soin, les pratiques des familles et le niveau d'égalité entre hommes et femmes, qui peuvent mutuellement renforcer ou affaiblir leurs effets (Crompton et Le Feuvre, 2000). Les pays d'Europe du Sud offrent peut-être la meilleure illustration de ces interrelations, puisque les progrès impressionnants des droits des femmes au cours des toutes dernières décennies contrastent avec la pauvreté des politiques de soutien au soin des enfants et des personnes âgées (Catarino et Oso, 2000;Lazaridis, 2007;Torres, 2008;León, 2010;Stefanelli, 2012). Il faut garder en mémoire les grandes évolutions historiques et institutionnelles qui montrent dans quelle mesure les politiques de soin ont été reconnues comme un terrain légitime de revendications pour la justice sociale et l'égalité (Williams, 2010b).…”
Section: Discussionunclassified